Computer system failure: planning disaster recovery. - Poker AM (Nursing Management)
A disaster recovery plan (DRP) defines the scope of restoration, establishes responsibilities and lists specific actions to be taken after the disaster. Although not actually involved in a DRP or computer systems, nurse managers must understand the steps involved and identify and communicate nursing's requirements.